La synchronie à lumière de la diachronie : quelques exemples - Rouanne, Laurence (Studia Romanica Posnaniensia, 2012)
This article aims to give various examples that illustrate the use of a bipolar and joint perspective – diachronic and synchronic – for the semantic study of certain items of the language. We are initially interested in the adverb carrément, which currently seems to bear little relation to any meaning as an adverb of manner. Nevertheless, the diachronic study shows how the latter stages of its development with respect to its root carré pave the way for its becoming a polyphonic adverb. It is a similar case with apparemment: it has four clear stages of semantic development, each of which is related to the various values of this adverb in synchrony. However what is perhaps even more revealing is the diachronic approach in the case of the delocutive adverbs (diablement, bigrement, fichtrement...), whereby it might be seen that these elements can have no nominal or adjectival base, which is one of the criteria that helps to illustrate their origin.